Infestasi pinjal dan infeksi Dipylidium caninum Linnaeus pada kucing liar di lingkungan kampus Institut Pertanian Bogor, Kecamatan Dramaga - Aulia Syifak Bashofi; Susi Soviana; Yusuf Ridwan (Perhimpunan Entomologi Indonesia, 2015)
This study was conducted to investigate flea infestation and Dipylidium caninum (Linnaeus 1758) infection on stray cat on Bogor Agricultural University Dramaga. Thirty stray cats were collected from various places around on Bogor Agricultural University Dramaga. The stray cats that showed clinical signs of pruritus and alopecia were collected purposively. The whole body was powdered by gamexan powder, after that the fleas were collected by manual and examined microscopically. The totals of 30 fecal stray cat samples collected and examined toward D. caninum used Mcmaster methode, flotation methode, and saw the existence of proglottid. The result of identification showed that there was found one species of flea, namely Ctenocephalides felis (Bouche 1835), while on faeces was not found D. caninum. Twenty one stray cats were infected by the flea with density average of fleas per cat was 3.8 ± 1.9 individual.